1975
DOI: 10.1530/jrf.0.0440077
|View full text |Cite
|
Sign up to set email alerts
|

Egg Transfer in the Cow: Factors Affecting Pregnancy and Twinning Rates Following Bilateral Transfers

Abstract: A total of 112 heifers was used in an egg transfer study to examine some of the factors affecting egg survival and twinning rates following bilateral transfers. Seventy-two recipient heifers were involved and pregnancy rates of 82\m=.\0%,66\m=.\7% and 61\m=.\5% were recorded for recipients in oestrus on the same day as (Day 0), 1 day before (Day +1) and 1 day after (Day \m=-\1) the donor respectively. Short-term (10-day) intravaginal progesterone, or intramuscular prostaglandin treatments for synchronization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1977
1977
2000
2000

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Rowson et al (1971) suggested that competition between embryos within a single uterine horn seemed to occur after unilateral transfer of two embryos. Rowson et al (1972) (Rowson et ai, 1971;Sreenan et al, 1975Sreenan et al, , 1978Anderson et al, 1978) and with that reported after unilateral transfer of two embryos (Boland et ai, 1975;Testart et ai, 1975 (Rowson et al, 1969;Hasler et al, 1987 (Shea, 1981;Lindner & Wright, 1983;King et al, 1985;Hasler et al, 1987). The transfer of embryos produced in vitro evaluated as morphologically excellent, good or fair, resulted in a higher pregnancy rate than the transfer of poor embryos ( Table 2).…”
Section: Pregnancy Diagnosismentioning
confidence: 78%
“…Rowson et al (1971) suggested that competition between embryos within a single uterine horn seemed to occur after unilateral transfer of two embryos. Rowson et al (1972) (Rowson et ai, 1971;Sreenan et al, 1975Sreenan et al, , 1978Anderson et al, 1978) and with that reported after unilateral transfer of two embryos (Boland et ai, 1975;Testart et ai, 1975 (Rowson et al, 1969;Hasler et al, 1987 (Shea, 1981;Lindner & Wright, 1983;King et al, 1985;Hasler et al, 1987). The transfer of embryos produced in vitro evaluated as morphologically excellent, good or fair, resulted in a higher pregnancy rate than the transfer of poor embryos ( Table 2).…”
Section: Pregnancy Diagnosismentioning
confidence: 78%
“…It has been confirmed that a higher incidence of twin pregnancy can be induced in beef heifers by bilateral embryo transfer than by unilateral transfer [8,11], although Sreenan and Diskin [26] showed no difference in the twin pregnancy, twin calving or overall embryonic mortality rates between unilateral and bilateral embryo distribution. Unlike pigs or ewes, transuterine migration of ova or embryos rarely occurs in cattle [27].…”
Section: Discussionmentioning
confidence: 91%
“…The definitive method of twin production by embryo transfer still remains unestablished, although several factors influencing the success of twin pregnancy have been previously elucidated [8].…”
mentioning
confidence: 99%
“…This appeared to be the result of competition between embryos within a single uterine horn. Other workers have confirmed the high pregnancy and twinning rate which may be achieved after bilateral embryo transfer (Sreenan, Beehan & Mulvehill, 1975) which appears therefore to be the method of choice for inducing twin pregnancy. In practice, because economic considerations preclude the use of surgery, twinning would only be induced by non-surgical methods: (1) one embryo may be placed non-surgically into the contralateral horn of a previously inseminated recipient (Boland, Crosby & Gordon, 1975;Boland & Gordon, 1978;Sreenan, 1978) or (2) one embryo may be transferred into each uterine horn (Heyman, Renard, Ozil & du Mesnil du Buisson, 1978).…”
Section: Introductionmentioning
confidence: 84%